Pengaruh Metode Bercerita terhadap Kemampuan Menulis Narasi pada Siswa Kelas 3 Sekolah Dasar - Syahada, Nathania Alyfa (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
In this research, we examined the influence of storytelling methods on the narrative writing abilities of third-grade students. The study involved students participating in various storytelling activities as a teaching approach. Data were collected through narrative writing tests before and after the intervention. The data analysis results indicated a significant improvement in narrative writing skills after the introduction of storytelling methods. Evaluation took into account factors such as creativity, narrative structure, and vocabulary usage. Implications of these findings include recommendations to incorporate storytelling methods as a learning strategy to enhance narrative writing skills at the elementary school level. This study contributes to a practical understanding of the implementation of storytelling methods in elementary education and emphasizes the importance of developing engaging learning strategies to enhance students' literacy skills.